Effects of additional action observation to an exercise program in patients with chronic pain due to knee osteoarthritis: A randomized-controlled trial - Öztürk, Özgül; Bombacı, Hasan; Keçeci, Tolga; Algun, Zeliha Candan (Elsevier Ltd, 2021)
Background: Knee osteoarthritis (OA) leads to pain, stiffness, and functional impairment and eventually decreased level of the quality of life. Although several treatment methods have been used to achieve pain relief, patients still complain of pain. Objective: The aim of this study was to investigate the effects of the addition of action observation therapy to an exercise program on pain severity, pressure pain threshold, kinesiphobia functionality, and pain catastrophization in knee OA patients with chronic pain. Methods: This prospective, randomized-controlled, superiority trial included a total of 36 patients with knee OA. The patients were randomly divided into two groups as the treatment group (n = 18) receiving action observation therapy in addition to exercise and control group (n = 18) receiving exercise alone. The interventions were performed three times weekly for six weeks. The primary outcomes were pain and pressure pain threshold. Secondary outcomes were kinesiphobia, functionality, and pain catastrophization. All participants were assessed at baseline (pre-intervention) and after the six-week treatment (post-intervention). Results: There was no significant difference in the primary and secondary outcome measures before and after the intervention between the groups (p > 0.05). Both groups showed a significant improvement in all outcome measures after the intervention (p < 0.01). Conclusion: Our study results suggest that action observation therapy in addition to an exercise program does not contribute any additional benefits to pain, pressure pain threshold, kinesiophobia, pain catastrophization, and functionality in knee OA patients with chronic pain. Nonetheless, further large-scale, long-term, prospective studies are needed to gain a better understanding on this subject.
Keywords: Knee Osteoarthritis; Action Observation; Chronic Pain; Exercise